Facilitating learning : a metacognitive process - Lucas, Maria Rita D.; Corpuz, Brenda B. (Manila, Philippines : Lorimar Publishing Company Inc., 2013)
This book on Facilitating Learning: A Metacognitive Process aims to align teacher education with the CHED- prescribed new teacher education curriculum that is reflective of the National Competency-Based Teachers Standards with the end in view of contributing to the formation of the ideal professional teacher as a concretely described in the seven integrated domains of the teaching and learning process. The activities or exercises at the end of every lesson were intended not only for drill and evaluative purposes but also for purposes of advocacy for current trends in education such as reflective education, multiple intelligence, multicultural education, interactive and brain-based teaching, authentic assessment and of bridging in the gap between theory and practice.
Part 1. Introduction -- Part 2. Focus on the Learner -- Part 3. Focus on Learning -- Part 4. Focus on classroom Processes -- Part 5. Integration
Includes bibliographical references.
Keywords: TEACHING